The Effect of Inquiry Teaching Method on Students’ Vocabulary Achievement - Henti Rezki Sempurna Harahap; Ahmad Ripai Rangkuty; Linda Efrina Nasution (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
The objective of this research is to determine whether there is a significant effect of using the Inquiry teaching method on students' vocabulary achievement among the seventh-grade students of SMP Negeri 1 Barumun. The population of this research is the seventh-grade students of SMP Negeri 1 Barumun, which consists of 54 students, and the sample was taken by cluster sampling composed of 27 students. This research is carried out by using experimental methods. The test is used as the instrument of this research, after collecting the data, it was analyzed using the t.test formula. The data analysis found that the mean or average of students' scores after the treatment is 80.55. Using the statistical analysis, the researchers get to 28.80, where the value of t.table  is 2.05. It means that the value of t observed is greater than that of the t table (to = 28.80> t table = 2.05). The calculation of the coefficient of determination is 0.84, which means the inquiry teaching method affected students' vocabulary achievement by as much as 84%. It means that the Inquiry teaching method significantly affects teaching vocabulary. The alternative hypothesis of this research is accepted, and the Inquiry teaching method can be applied in the classroom to increase the student's vocabulary achievement.